2017
DOI: 10.4149/neo_2017_214
|View full text |Cite
|
Sign up to set email alerts
|

New concept of the Axin2 rs2240308 polymorphism and cancer risk: an updated meta-analysis

et al.

Abstract: Previous meta-analyses reported that the variant T allele of Axin2 rs2240308 is associated with a decreased cancer risk. However, more recent findings have been inconsistent. Therefore, we carried out an updated meta-analysis to examine whether this polymorphism is still associated with a decreased cancer risk. Twelve articles, including 14 case-control studies (2,215 cases and 2,481 controls), were included in our study. Surprisingly, different from previous meta-analyses, no significant association between A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…24 Significant differences have been reported in the association between rs2240308 and the risk of cancer for type of cancer and ethnic group. 17 Then, while it has been reported that rs2240308 increased the risk of lung cancer especially in Asian population, 5 a recent analysis indicated that AXIN2 148 C > T (rs2240308) variant may be associated with decrease lung risk in Asian and Caucasian populations. 25 Therefore, further studies in Latin American population should be conducted to explain the association between AXIN2 polymorphisms and CRC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…24 Significant differences have been reported in the association between rs2240308 and the risk of cancer for type of cancer and ethnic group. 17 Then, while it has been reported that rs2240308 increased the risk of lung cancer especially in Asian population, 5 a recent analysis indicated that AXIN2 148 C > T (rs2240308) variant may be associated with decrease lung risk in Asian and Caucasian populations. 25 Therefore, further studies in Latin American population should be conducted to explain the association between AXIN2 polymorphisms and CRC.…”
Section: Discussionmentioning
confidence: 99%
“…This polymorphism (rs2240308, c.148 G > A) results in an amino acid change from proline to a serine. Although, rs2240308 has been associated with hypodontia and cancer in different populations, 16,17 in Iranian subjects, this polymorphism was related with decreased risk for CRC. 18 The inconsistent results reported in literature are explained by racial differences.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…P < 0.1 meant a significant heterogeneity, and if so, we used the random effects model (DerSimonian and Laird methods) to summarize the data [20]; if not, the fixed effect model (Mantel-Haenszel method) was selected [21]. Hardy-Weinberg equilibrium (HWE) was performed for sensitivity analysis [22].…”
Section: Discussionmentioning
confidence: 99%
“…If P < 0.05, indicating that a significant heterogeneity was found, we employed the random-effects model (DerSimonian–Laird method) [34]. On the other hand, the fixed-effects model (Mantel–Haenszel method) was carried out [35]. We adopted qualitative funnel plot to assess possible publication bias by calculating the standard error of log(OR) for each research plotted against its log(OR).…”
Section: Methodsmentioning
confidence: 99%